Integral conditions for the invertibility of Markov chains on a half-line with general measure of irreducibility - Isakova, T. I.; Filonov, Yu. P. (Ukrains’kyi Matematychnyi Zhurnal, 2004)
We present conditions for the invertibility of Markov chains with values from ℝ+ and general measure of irreducibility. The results are obtained by the classical method of test functions combined with the method of perturbation of partial potentials.